(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to determine the effects of abduction in the community at Barangay Pasong Putik Quezon City. The study utilizes a descriptive research method, which was used to gather information from respondents in accordance with the posed questions. The results of this study show that abduction had an effect on the community, and it can also affect their daily lives. The result also revealed that the effects might be psychological and behavioral effects that can lead to poor communication with others and a lack of socializing. This study recommended that the barangay should conduct seminars for its residents with regard to what to do when there’s an abduction, as stated in our background of the study. Abductions may happen at any time of any day or night, at we least expect them to; the barangay has helped to take care of its citizens by giving them the knowledge they need to lessen or prevent any worst-case scenarios during such an event. It’s not just the Philippines that is experiencing an increase in abductions; there are other nations that are also experiencing this problem. Abductions are becoming more unpredictable by the day; it’s preferable to be ready for the worst rather than hoping for the best and suffering the effects later. The implications of this study could be used to determine how the abduction can affect every individual who experienced abduction and how they will manage to support and help others who encounter the abduction.